Unformatted text preview: Z e 2 x 3 p 1 + e 2 x dx: Solution. Let u = 1 + e 2 x , so du = 2 e 2 x dx . Thus Z e 2 x 3 p 1 + e 2 x dx = 1 2 Z 3 p 1 + e 2 x (2 e 2 x ) dx = 1 2 Z 3 p udu = 1 2 ± 3 4 u 4 = 3 + C = 3 8 & 1 + e 2 x ± 4 = 3 + C: Remark. You have the choice of using the "crutch" of solving for " dx " in terms of " du " (as indictated in the solution of 1( a ) ) or determining the conversion factor mentally (as in the solution for 2). 1...
View
Full Document
 Spring '09
 CHEUNG
 Math, Calculus, 3 pts, 5 pts, 2 pts

Click to edit the document details